2001
DOI: 10.1037/h0095091
|View full text |Cite
|
Sign up to set email alerts
|

A statewide assessment of psychosocial rehabilitation programs: General characteristics and services.

Abstract: Psychosocial rehabilitation (PSR) encompasses a diverse array of skill-building and environmental support services for individuals with serious mental illness. The current study gleaned information from state Department of Mental Heath (DMH) databases and interviews with program directors to describe general characteristics and services of 22 out of 24 PSR programs in one New England state. Results underscored the relative predominance of services targeting social rehabilitation rather than vocational, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Clubhouse members reported an average of 5.6 years since their last psychiatric hospital admission. These characteristics are similar to other studies involving consumers of psychosocial rehabilitation programs (Macias, Jackson, Schroeder, & Wang, 1999;Lucca & Allen, 2001). …”
Section: Samplesupporting
confidence: 81%
See 1 more Smart Citation
“…Clubhouse members reported an average of 5.6 years since their last psychiatric hospital admission. These characteristics are similar to other studies involving consumers of psychosocial rehabilitation programs (Macias, Jackson, Schroeder, & Wang, 1999;Lucca & Allen, 2001). …”
Section: Samplesupporting
confidence: 81%
“…These programs strive to increase social connections among consumers most at risk for isolation and the associated effects. Nearly all clubhouse programs emphasize social and recreational opportunities for its membership-a consistent feature of clubhouses in the current study (Lucca & Allen, 2001;Macias, Jackson, Schroeder, & Wang, 1999).…”
Section: Defining and Measuring Social Network Supportmentioning
confidence: 91%
“…Clubhouses characterized by a greater proportion of late to middle-aged members and a greater percentage of individuals living with psychoses are associated with environments that emphasize less member involvement and facilitate less personal growth (Moos 1996;Mowbray et al 2006). This fact is especially compelling given that the average age of a clubhouse member is between 30 and 50, and living with a serious form of mental illness, such as schizophrenia (Lucca and Allen 2001;Macias et al 1999;Pernice-Duca 2008). Gender has also been implicated as a highly determinative factor in determining the quality of the social climate of treatment programs.…”
Section: The Clubhouse Modelmentioning
confidence: 96%
“…Overall, members and staff indicated that clubhouses did not offer formal substance abuse assistance, activities for families, medication management, housing assistance, or emergency services were not routinely offered or practiced. This comes as no surprise since many clubhouses offer services in social, vocational, educational, and residential domains whereas very few offer direct medical or psychological services to their members (Lucca and Allen 2001;Hargreaves et al 2007). However, contrary to expectations, members were more likely than staff to perceive the clubhouse providing assistance with housing and medication management.…”
Section: Comparing Staff and Member Evaluations Of The Program Enviromentioning
confidence: 96%
See 1 more Smart Citation